The Effect of Therapeutic Communication on Social Interaction in Social Isolation Patientsthe Results of Schizophreniaat the Phalamartha Center Sukabumi the Year 2022 - Dian Noviati Kurniasih; Nurhefi; Zainal Abidinsah; Lailia Fatkul Jannah (International Journal of Scientific Multidisciplinary Research, 2023)
Social isolation is an attempt to avoid interaction with other people or avoid contact with other people and is an act of releasing both attention and interest in the immediate social environment, which can be temporary or permanent